2023
DOI: 10.1021/acsanm.2c05566
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl Naphthalocyanine-Doped Polymer Dots for Near-Infrared Light-Induced Nitric Oxide Release and Bactericidal Effects

Abstract: The development of efficient antibacterial agents is important for public health. To completely damage bacteria in situ, light has been used as an external stimulus, but the wavelength range of light is limited up to visible light at which the antimicrobial activity is incomplete. Here, we report on our investigation of the bactericidal effect of heat and nitric oxide (NO) generated simultaneously by near-infrared (NIR) light using vanadyl naphthalocyanine-doped polymer dots (Pdots). P-dots co-doped with vanad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These nanoparticles did not require biotoxic co-solvents to dissolve metal complexes or organic compounds. Since it was reported that P-dots of similar composition were applied in cellulo without remarkable toxicity, 22 and another study showed that P-dots could release NO via the photo-thermal pathway to show an antibacterial effect, 26 our P-dots are expected to be useful tools for investigating the mechanisms of diverse biological effects of NO.…”
Section: Discussionmentioning
confidence: 83%
“…These nanoparticles did not require biotoxic co-solvents to dissolve metal complexes or organic compounds. Since it was reported that P-dots of similar composition were applied in cellulo without remarkable toxicity, 22 and another study showed that P-dots could release NO via the photo-thermal pathway to show an antibacterial effect, 26 our P-dots are expected to be useful tools for investigating the mechanisms of diverse biological effects of NO.…”
Section: Discussionmentioning
confidence: 83%
“…N -Nitrosamines display phototriggered NO release due to the homolytic cleavage of the N–NO bond. , N -Nitrosamine-based napthalimide derivatives form an anilinyl radical byproduct after homolytic cleavage and subsequently transform back into the original naphthalimide derivative . Following the development of NOD and BCPx-NO , we explored the NO release mechanism and the consequential fluorescence enhancement due to the generation of SM-3 and BCPx , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…80 Recently, Liu and co-workers reported a NIR light-induced vanadyl naphthalocyanine and N-nitrosamines (1, 2, 3) doped polymer dots as antibacterial agents (P-dots). 81 The polymer dot consists of polystyrene graft ethylene oxide functionalized with carboxy (PEG-COOH, weight-average molar mass (M w ) = 36 500 g/mol) and poly(9-vinylcarbazole) (PVK, M w = 25,000−50 000 g/mol) polymers. Upon exposure to 808 nm NIR laser light irradiation, the polymer dots released NO from N-nitrosamine compounds and simultaneously generated heat from vanadyl naphthalocyanine.…”
Section: Small Molecular N-nitrosamine Encapsulated Polymersmentioning
confidence: 99%